A brush with death : an artist in the death camps - Wyszogrod, Morris, 1920- (Albany : State University of New York Press, 1999)
"In this memoir Morris Wyszogrod recounts his experiences from the time of the Nazi invasion of Poland to the liberation of the Theresienstadt concentration camp."
Includes index.
Print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Wyszogrod, Morris, -- 1920-; Wyszogrod, Morris, -- 1920-; Jews -- Poland -- Warsaw -- Biography; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Personal narratives; Holocaust, Jewish (1939-1945), in art; Warsaw (Poland) -- Biography; Juifs -- Pologne -- Varsovie -- Biographies; Holocauste, 1939-1945 -- Pologne -- Varsovie -- Récits personnels; Holocauste, 1939-1945, dans l'art.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Holocaust; Holocaust, Jewish (1939-1945) in art; Jews; Poland -- Warsaw; Judenvernichtung; Künstler; 1939-1945; Autobiography; Personal Narrative; Biography; autobiographies (literary works); Autobiographies; Biographies; Personal narratives; Autobiographies; Personal narratives; Biographies; Autobiographies; Récits personnels; Biographies